(untitled) - Johnstone, William W.; Johnstone, J.A. (Thorndike, ME, 2023)
From the greatest western writers of the 21st century, the second adventure featuring circuit rider Taylor Callahan. a mysterious man in black who rides from town to town with a bible in hand and guns in his holsters, delivering the word of God and hard-fought justice.
Keywords: Circuit riders; West (U.S.); Fiction; United States marshals; Fiction; Western fiction